Infantile bloody nipple discharge: A case report and review of the literature - Gupta Vipul; Yadav Sunil (Wolters Kluwer Medknow Publications, 2009)
Bloody nipple discharge is described as an extremely rare clinical entity in a 7-month-old infant managed conservatively. The authors discuss the management protocol of this rare clinical presentation along with the pertinent literature.